Synthesis and Evaluation of a Class of Compounds Inhibiting the Growth of Stromal Antigen 2 (STAG2)‐Mutant Ewing Sarcoma Cells. (19th February 2022) - Zhang, Nenggang; Lin, Keng‐Fu; Yang, Christian; Peruski, Scott; Pati, Debananda; Gilbertson, Scott R.
Abstract: STAG2 (SA2) is a critical component of the cohesin complex that regulates gene expression and the separation of sister chromatids in cells. Mutations in STAG2 have been identified in over thirty different types of cancers including myeloid leukaemia, non‐small cell lung, bladder and Ewing sarcoma. Selectively inhibiting cancer cells lacking of STAG2 is an attractive approach for the cancer therapy. Here we report that a small molecule, StagX1, identified through a high‐throughput screening, inhibits the growth of Ewing sarcoma cells possessing mutant STAG2 . A new synthetic route to the StagX1 scaffold and new versions of the molecule along with their activity in a cell viability assay are reported. Abstract : Going STAG : Selectively inhibiting cancer cells that lack stromal antigen 2 (STAG2) is an attractive approach for cancer therapy, particularly Ewing sarcoma. Herein we report a small‐molecule, StagX1, and the synthesis of derivatives of such by a new route. These compounds selectively inhibit cancer cells that lack STAG2.